Alan J. Lichtmann: The Embattled Vote in America. From the Founding to the Present - Cora, Zoltán (AMERICANA E-journal of American Studies in Hungary, 2020)
The Embattled Vote in America. From the Founding to the Present Alan J. Lichtmann Cambridge, Massachusetts: Harvard University Press 315 pages